NEED ANALYSIS OF GUIDANCE AND COUNSELING TEACHERS TOWARDS CYBER COUNSELING TRAINING - Aswar Aswar; M. Amirullah; Akhmad Harum; Edil Wijaya Nur (Universitas Pendidikan Indonesia, 2022)
During the Covid-19 pandemic, guidance and counseling teachers in the field faced a difficult situation, forcing them to provide online services to students. This study aims to analyze the needs of guidance and counseling teachers for cyber counseling training. The research method used is a qualitative approach by applying empirical phenomenological research. Data were obtained through direct interviews offline and online (Whatsapp) with 9 (nine) research subjects. The data analysis technique used is Interpretative Phenomenological Analysis (IPA). The results of the study indicate that guidance and counseling (BK) teachers need cyber counseling training, analyzed in several aspects, including: (1) Barriers, which are indicated by (a) BK teachers have difficulty interpreting students' non-verbal language when providing online-based services; (b) constrained by the stability of the internet network; and (c) the minimum internet quota owned by students; (2) Insights and attitudes, which are indicated by: (a) BK teachers do not know anything at all and do not provide online-based services, (mainly by old BK teachers); (b) knowing but confused in starting and doing; (c) positive thinking, utilizing creativity, and daring to start even though they have not mastered the conceptual framework and praxis (mainly carried out by young BK teachers); (3) Needs, where the aspects needed by BK teachers for cyber counseling training include: (a) online-based individual counseling service construction; (b) how to make online assessments that are attractive to students; (c) how to provide effective and efficient services, starting from material preparation, media selection, approach selection, strategy, communication techniques, procedures, and service evaluation.